The importance of therapist/client ethnic/racial matching in couples treatment for domestic violence - Horst, K.; Mendez, M.; Culver-Turner, R.; Amanor-Boadu, Yvonne; Minner, B.; Cook, J.; Stith, Sandra M.; McCollum, E. (My University, 2012)
Outcome research indicates a relative degree of variability regarding the effectiveness of client and therapist ethnic/racial matching (see Cabral and Smith 2011, Shin et al. 2005). Considering these findings, our study hopes to further understand the complexity behind ethnic/racial matching in treatment. In this study, we examined interviews with clients and therapists regarding ethnic/racial matching in couples treatment for domestic violence (e.g., McCollum and Stith 2008). Our findings indicated that ethnic/racial matching is a complex multi-faceted issue and connected ethnic/racial matching with issues of culture, human experience, and others. We recommend clinicians consider the complexity of ethnic/racial matching in practice.
Keywords: Race/ethnicity; Racial/ethnic matching; Racial/ethnic matching in family therapy; Race/ethnicity in family therapy; Domestic violence; Couples treatment for domestic violence; Therapeutic relationship; Qualitative methodology